Electrospun Nanofibers With pH-Responsive Coatings for Control of Release Kinetics - Sayin, Sezin; Tufani, Ali; Emanet, Melis; Genchi, Giada Graziana; Sen, Ozlem; Shemshad, Sepideh; Ozdemir, Ece; Ciofani, Gianni; Ozaydin Ince, Gozde (Frontiers in Bioengineering and Biotechnology, 2019)
Functional and stimuli-responsive nanofibers with an enhanced surface area/volume ratio provide controlled and triggered drug release with higher efficacy. In this study, chemotherapeutic agent Rose Bengal (RB) (4,5,6,7-tetrachloro-2’,4’,5’,7’-tetraiodofluoresceindisodium) loaded water soluble polyvinyl alcohol (PVA) nanofibers were synthesized by using the electrospinning method. A thin layer of poly(4-vinylpyridine-co-ethylene glycol dimethacrylate) p(4VP-co-EGDMA) was deposited on the RB loaded nanofibers (PVA-RB) via initiated chemical vapor deposition (iCVD), coating the fiber surfaces to provide controllable solubility and pH response to the nanofibers. The uncoated and (p(4VP-co-EGDMA)-PVA) coated PVA-RB nanofiber mats were studied at different pH values to analyze their degradation and drug release profiles. The coated nanofibers demonstrated high stability at neutral and basic pH values for long incubation durations of 72 hours, whereas the uncoated nanofibers dissolved in less than 2 hours. The drug release studies showed that the RB release from coated PVA-RB nanofibers was higher at neutral and basic pH values, and proportional to the pH of the solution, whereas the degradation and RB release rates from the uncoated PVA-RB nanofibers were significantly higher and did not depend on the pH of environment. Further analysis of the release kinetics using the Peppas model showed that while polymer swelling and dissolution were the dominant mechanisms for the uncoated nanofibers, for the coated nanofibers Fickian diffusion was the dominant release mechanism. The biocompatibility and therapeutic efficiency of the coated PVA-RB nanofibers against brain cancer was investigated on glioblastoma multiforme cancer cells (U87MG). The coated PVA nanofibers were observed to be highly biocompatible and they significantly stimulated the ROS production in cells, increasing apoptosis. These promising results confirmed the therapeutic activity of the coated PVA-RB nanofibers on brain cancer cells, and encouraged their further evaluation as drug carrier structures in brain cancer treatment.